Alternative designs of load−sharing cobalt chromium graded femoral stems. (September 2017) - Limmahakhun, Sakkadech; Oloyede, Adekunle; Chantarapanich, Nattapon; Jiamwatthanachai, Pongnarin; Sitthiseripratip, Kriskrai; Xiao, Yin; Yan, Cheng
Graphical abstract: Highlights: CoCr graded femoral stems attain reduced bone-stress shielding, stability, and bone-equivalent stiffness, in silico and in vitro. . Reversed AGS model failed balanced bone-implant micromotions on promoting bone osseointegration. Dense RGS, hollow RGS, and proximal AGS increased Gruen zone 7 stress values by 3 − 4.7 times that of Ti stems. Proximal AGS and hollow RGS are highlighted to be adopted for an innovative load-sharing femoral stems. Abstract: The incapability of controlling relative micromotions and load transfers to a peri -prosthetic femur shortens implant longevity. This study aims to evaluate the possibility of applying graded porous cobalt chromium (CoCr) to cementless femoral stems. 3D finite element analyses and physical testings of hip implants were conducted with four different grading orientations, along the axial and radial planes of the femoral stem. The results show that the CoCr graded femoral stems with a porosity decreased caudally and inwardly may control the relative micromotions in an acceptable range for bone ingrowth, significantly increase stress transfers on the Gruen zone 1 and 7, and attain the flexural stiffness comparable to human femurs. Therefore, CoCr graded femoral stems demonstrate great potential for applications in implants with reduced stress shielding and improved long-term survival rates.